Dexmedetomidine, high-flow nasal oxygen and sugammadex-reversal of rocuronium: overcoming anaesthetic challenges in a parturient with congenital muscular dystrophy presenting for caesarean section. (May 2018) - Creaney, M.; Moriarty, RM.; Milner, M.; Murphy, C.
Highlights: Parturients with congenital muscular dystrophy may have limited neuraxial access. Severe respiratory muscle weakness hinders weaning from mechanical ventilation. Dexmedetomidine provides sedation and anxiolysis without respiratory depression. High-flow nasal oxygen assists apnoeic oxygenation during intubation. Profound neuromuscular blockade with rocuronium can be reversed with sugammadex. Abstract: Congenital muscular dystrophies are characterised by progressive skeletal muscle weakness from birth or early infancy. Maternal respiratory compromise, joint contractures and presence of spinal instrumentation or fusion are some of the anaesthetic challenges that may be encountered in the obstetric setting. The choice of anaesthetic technique for surgical delivery needs to be considered on an individual basis. Multidisciplinary involvement is paramount to optimise peripartum care and outcomes. In this case report, we present the use of dexmedetomidine, humidified high-flow nasal oxygen, rocuronium and sugammadex in the anaesthetic management of a wheelchair-bound, non-invasive bilevel positive airway pressure ventilation-dependent parturient with congenital muscular dystrophy, who was presenting for caesarean section.